Geohistória e a espacialização do exército brasileiro no Estado de Roraima : 1992-2018 - Gomes, Marcos de Lima (2020)
The present research brings a geohistorical and geopolitical military study about the spatialization of the Brazilian Army in the state of Roraima from phenomena that, over time, influenced the expansion of Military Power in this region, through relocations and / or transfers of Military Organizations from large centers to the Legal Amazon. Therefore, the objective is to carry out an analysis of the geohistory and spatialization of the Brazilian Army in the state of Roraima, based on a case study of the 1st Jungle Infantry Brigade, based in the city of Boa Vista (RR), since its inception. creation in 1992 until 2018. As methodological procedures, they classify as exploratory-descriptive-explanatory in terms of ends and quali-quantitative in terms of means, instrumentalized by means of a hypothetical-deductive method, based on data collection from a integrative, bibliographic, bibliometric and documentary review, and a case study, ending with a data analysis based on geographic hermeneutics, discourse, graphical and geospatial analysis, which materialized in triangulation analysis, based on dialogue with the state of art, survey of empirical data, and analysis of the situation. The results of the research on the subject in question, point to a diachronic sequence, among them: a systematic and integrative analysis of the concepts of Political Geography and Geopolitics and the life cycle evolutions of 33,073 scientific productions resulting in a study of the state of the art ; presents a summary table of a systematic and integrative review of the concepts raised with an emphasis on the Amazon; presents a map of the 65 military fortifications in the Amazon (16th-19th centuries); brings a geohistorical framework about the Amazon based on the literature on the Caribbean Amazon; it brings scientific contribution through a case study through a geopolitical study of the Military Power of the Brazilian Army in Roraima, as well as a diagnosis of deficit in the Military Power existing in the state of Roraima at two different moments in its historiography. Finally, it is concluded based on the results presented in this dissertation that the slow process of expansion of Military Power in the state of Roraima happens through geohistorical-political-military events that transformed the region, which would culminate in the creation of the 1st Brigade of Selva Infantry in 1992 and the incomplete power of force in the state of Roraima due to structural problems and incongruencies of the Brazilian State in prioritizing the Legal Amazon.